2021
DOI: 10.3389/fpsyg.2021.663447
|View full text |Cite
|
Sign up to set email alerts
|

The Strengths and Barriers Recovery Scale (SABRS): Relationships Matter in Building Strengths and Overcoming Barriers

Abstract: There is a well-established relationship between isolation and both morbidity and mortality in the context of addiction recovery, yet the protective effects of intimate and familial relationships have not been adequately assessed. The current paper uses the European Life In Recovery database to assess the association between relationship status and living with dependent children on recovery capital of people in recovery from drug addiction, operationalised by the Strengths And Barriers Recovery Scale (SABRS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 36 publications
1
10
0
3
Order By: Relevance
“…Although families have been identified as a primary context of care for young adults' substance use treatment processes (129), this study showed that the family context among adult children of parents with SUDs is often not facilitative for their treatment and recovery processes. In line with evidence on the importance of relationships and social resources needed for initiation and maintenance of addiction recovery (130)(131)(132)(133)(134)(135)(136)(137), this study confirms the importance of interpersonal relationships and social resources in readiness to change and early stages of recovery (131,(138)(139)(140)(141)(142)(143). Although the importance of social networks in improving early and more sustained recovery outcomes has been established (144), this study provides insight in how family, parent and peer support systems can both inhibit and encourage recovery in offspring of parents with SUDs.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although families have been identified as a primary context of care for young adults' substance use treatment processes (129), this study showed that the family context among adult children of parents with SUDs is often not facilitative for their treatment and recovery processes. In line with evidence on the importance of relationships and social resources needed for initiation and maintenance of addiction recovery (130)(131)(132)(133)(134)(135)(136)(137), this study confirms the importance of interpersonal relationships and social resources in readiness to change and early stages of recovery (131,(138)(139)(140)(141)(142)(143). Although the importance of social networks in improving early and more sustained recovery outcomes has been established (144), this study provides insight in how family, parent and peer support systems can both inhibit and encourage recovery in offspring of parents with SUDs.…”
Section: Discussionsupporting
confidence: 82%
“…Although the importance of social networks in improving early and more sustained recovery outcomes has been established (144), this study provides insight in how family, parent and peer support systems can both inhibit and encourage recovery in offspring of parents with SUDs. Consequently, specific components of early recovery social networks, such as network size (133,139,145), quality (146), and density (138) have proven to be important factors in recovery outcomes. Strong associations have been found between ongoing contact with substance users and continued substance use (147).…”
Section: Discussionmentioning
confidence: 99%
“…Although abstinence may be an important feature, it is not a prerequisite for recovery (Laudet & White, 2010). The addiction recovery literature has grown quickly over the last few years, including a variety of recovery indicators, resources and instruments (Ashford et al, 2020;Best & Laudet, 2010;Best et al, 2021;Cano et al, 2017;Cloud & Granfield, 2008;Groshkova et al, 2013;Neale et al, 2016). Far less is known about how recovery takes place and which mechanisms and mediators are central to addiction recovery.…”
Section: Mechanisms and Mediators Of Addiction Recoverymentioning
confidence: 99%
“…Indeed, our study uses retrospective recall of past-behaviour using a cross-sectional survey which asks participants about historical and current information to then assess the “change” between the two. Additional information around the development of the SABRS scale and domains that form the LiR has been previously outlined elsewhere [ 6 , 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…This may indicate women’s capacity for developing a diverse range of skills across recovery stages, but this conclusion requires considerably more research and analyses across specific domains and resources. Another study by Best and colleagues [ 6 ] showed that the association between living with dependent children and reporting greater gains in recovery capital across the recovery journey is more significant in females compared to males, emphasising important gender differences in relation to the recovery trajectory. Still, there is a scarcity of research identifying which specific features of recovery capital show marked gendered differences across the recovery journey.…”
Section: Introductionmentioning
confidence: 99%